Opportunities and Challenges of Digital Learning Media During the Covid-19 Pandemic in Primary School - Jamilah Jamilah; Tri Sukitman; Moh. Fauzi; Jamilah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
During the Covid-19 Pandemic, the learning process used by teachers is in the form of digital media. This research is focused on digital learning, barriers faced by teachers, and various approaches to overcome various obstacles faced by teachers in implementing digital learning during the covid 19 pandemic. The type of research is qualitative research with a survey method. This research was conducted in Sumenep Regency with primary school teachers as the research object. The data collection consists of questionnaires given to 100 teachers and interviews to 9 teachers to describe information related to the focus of the research. The results of this study show that teachers do not directly utilize various digital platforms of various learning technologies implemented in online learning during covid 19. The obstacles experienced by the teachers include the teacher's low ability in applying the information technology, parents' economic factor, unstable internet networks, and the absence of information technology training given by schools. On the other hand, as time goes by teachers are able to implement the digital learning independently and adapt to the surrounding environment and understand the various characteristics of students in making use of digital in learning during the COVID-19 pandemic.